2018
DOI: 10.1016/j.jaerosci.2017.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Role of viral bioaerosols in nosocomial infections and measures for prevention and control

Abstract: A B S T R A C TThe presence of patients with diverse pathologies in hospitals results in an environment that can be rich in various microorganisms including respiratory and enteric viruses, leading to outbreaks in hospitals or spillover infections to the community. All hospital patients are at risk of nosocomial viral infections, but vulnerable groups such as older adults, children and immuno-compromised/-suppressed patients are at particular risk of severe outcomes including prolonged hospitalization or death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 147 publications
0
30
0
Order By: Relevance
“…In this perspective, new preventive solutions to mitigate the effects of airborne transmission might be needed, including suitably modified ventilation systems in synergy with powerful new filtering devices able to capture and/or inactivate the airborne microdroplets. [ 6,8–12 ] Indeed, several studies demonstrated that the transmission via aerosols is of great importance in the COVID‐19 pandemic caused by the SARS‐CoV‐2. [ 9 ] In particular, the SARS‐CoV‐2 virus is primarily released from the respiratory tract as an aerosol with droplets generated, for example, by exhalation, talking, sneezing, coughing, and it can be increasingly released through intubation, bronchoscopy, rhinoscopy, or surgical interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this perspective, new preventive solutions to mitigate the effects of airborne transmission might be needed, including suitably modified ventilation systems in synergy with powerful new filtering devices able to capture and/or inactivate the airborne microdroplets. [ 6,8–12 ] Indeed, several studies demonstrated that the transmission via aerosols is of great importance in the COVID‐19 pandemic caused by the SARS‐CoV‐2. [ 9 ] In particular, the SARS‐CoV‐2 virus is primarily released from the respiratory tract as an aerosol with droplets generated, for example, by exhalation, talking, sneezing, coughing, and it can be increasingly released through intubation, bronchoscopy, rhinoscopy, or surgical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In this perspective, new control technologies capable of inactivating aerosolized bacteria and viruses are highly sought after; these new technologies must be economically convenient, should not be responsible for secondary pollution, and must be able to effectively inactivate different types of pathogens. [ 8,17 ] However, the efficacy of treatments depends on genome structure of the pathogens and their replication machinery [ 18 ] ; furthermore, new technologies must take into account the possibility that both bacteria and viruses could develop harmful mutagenic outcomes associated with multiple transition mutations across the genome when they are underexposed or undergo insufficient inactivation treatments. [ 18,19 ]…”
Section: Introductionmentioning
confidence: 99%
“…(16) Nevertheless, HCWs should learn how to reduce risks associated with all aerosol delivery devices as not all drugs that are nebulized in the acute care setting are available in pMDIs, dry powder inhalers (DPIs), or soft mist inhalers (SMIs) such as antibiotics and prostaglandins. (17,18) Inhalers, such as pMDIs, have been suggested to present less risk than other medical aerosols, often without supporting evidence. (19,20) The rationale for reduced risk compared with other medical aerosols may be because drug is enclosed and less open to contamination than open cup nebulizers, and the low emitted dose (100 lL/actuation) produces less aerosol mass with shorter treatment times.…”
mentioning
confidence: 99%
“…For example, during the slit lamp or direct fundoscopy examination, an ophthalmology doctor need to directly face the patient at a distance of 3-10 cm. There is also huge risk of aerosol exposure during processes such as dental repair, open surgery, tracheal intubation and so on (51,52). A recent survey conducted in British ophthalmology practitioners showed that they were very unconfident about no ocular protection in the daily work and called for more eye protection (53).…”
Section: Discussionmentioning
confidence: 99%